Neutrophil Extracellular Traps (NETs) and Vasculitis - Arneth, Borros (Int J Med Sci, 2021)
Background: Neutrophil extracellular traps (NETs) have been implicated in host immune responses. Attempts have been made to examine how NETs affect the pathogenesis of complications such as autoimmune and vascular disorders. Aim: This study aimed to explore the relationship between NETs and vasculitis. Material and Methods: The current study entailed the searching of PsycINFO, PubMed, Web of Science, and CINAHL for articles related to the research topic. The search terms and phrases included “vasculitis,” “NETs,” “neutrophil extracellular traps,” “NETosis,” and “pathogenesis.” The search was limited to articles published between 2009 and 2019. Results: Researchers have shown that NETs contribute to the pathogenesis of vasculitis through different mechanisms and processes, including renal failure and vascular damage. The protective effects of NETs have also been highlighted. Discussion: Overall, some scholars have shown the effectiveness of using DNase I and the PAD4 inhibitor Cl-amidine to treat vasculitis by restricting NET formation. However, observations have been noted in only animal experimental models. Conclusion: Neutrophil hyperactivity and its role in vasculitis are not yet fully understood. More studies aiming to determine the accurate function of NETs in vasculitis pathogenesis, particularly in humans, should be undertaken. Intensive research on NETs and vasculitis can increase the knowledge of medical practitioners and contribute to the development of new treatment methods to enhance patient outcomes in the future.